Decomposition of nitric oxide by rhodium cluster cations at high temperatures. Issue 47 (29th November 2021) - Nagata, Toshiaki; Kawada, Kimihiro; Chen, Xuemei; Yamaguchi, Masato; Miyajima, Ken; Mafuné, Fumitaka
Abstract : Decomposition reactions of NO molecules on gas-phase Rh n + ( n = 6–9) clusters were investigated by gas-phase thermal desorption spectrometry and density functional theory calculations. Abstract : Decomposition reactions of NO molecules on gas-phase Rh n + ( n = 6–9) clusters were investigated by gas-phase thermal desorption spectrometry and density functional theory calculations. We found that NO adsorbs on the clusters, forming Rh n N x O x + at room temperature. Upon heating, NO desorption was observed below 800 K. Above 800 K, while for n = 7 and 8, each of Rh7 N3 O3 +, Rh7 N4 O4 +, and Rh8 N3 O3 + was found to release an N2 molecule, no N2 formation was clearly observed for Rh6, 9 N x O y + . We considered that both Rh7 N3 O3 + and Rh8 N3 O3 + have at least two dissociated NO molecules, while Rh6 N x O x + ( x = 1–3) has one or less. Our computational results for Rh8 N3 O3 + suggested that the formation of an N–N bond in the Rh8 N3 O3 + structure must overcome an energy barrier of ∼2 eV, which is the highest among the suggested possible reaction pathways. These findings suggested that the size-dependent activity of NO decomposition is governed primarily by how NO molecules are adsorbed on Rh n + clusters, i.e. whether two or more N atoms from dissociated NO molecules exist in the NO adsorbed clusters, and secondly, by the readiness of the N–N bond formation.